Is Responsive Sexual Desire for Partnered Sex Problematic among Men? Insights from a Two-Country Study - Štulhofer, Aleksandar (Array, 2013)
In contrast to the body of research focusing on female sexual desire, there has been very little research into patterns of male sexual desire. This study addresses this deficiency in the literature by providing empirical answers to the following three questions: (1) is there a pattern of responsive sexual desire – defined as being predominantly receptive to a partner’s initiation of sexual activity without initially desiring it – among men? (2) Is this pattern associated with lower levels of sexual health than a more spontaneous pattern of male desire? (3) Are existing clinical observations regarding possible causes of reduced interest in partnered sex useful for understanding the more responsive men’s sexual desire? A large online survey about men’s sexual interest was conducted in 2011 among 2215 Norwegian and Portuguese men aged 18–75 years (the average age in the sample was 36.5 years). Sociodemographic, health-related, sociosexual and relationship-related information was collected. Three distinct patterns of male sexual desire were observed: decreased (23.6%), responsive (2.5%) and spontaneous (73.9%) desire patterns. Men in the more responsive and spontaneous desire groups significantly differed from participants in the decreased desire group, as they reported significantly higher levels of sexual interest, sexual satisfaction and frequency of sexual intercourse and were less likely to have experienced sexual health difficulties in the past 12 months. Interestingly, participants with more responsive and spontaneous desire patterns were indistinguishable in terms of a number of sociodemographic, health-related, sociosexual and relationship-related variables. The sole predictor of the responsive sexual desire pattern was proneness to relationship-related sexual boredom. Clinical observations about the roles of negative emotions, relationship strain and specific sexual arousal patterns (homoerotic, autoerotic and/or paraphilic) in the etiology of hypoactive sexual desire did not seem relevant for men with responsive desire.